Effect of Inoculation with Arbuscular Mycorrhizal Fungi on Enhancing Root Growing Systems and Improved Nutrient Uptake Efficiency in Tomato - Collins, Tom (2023)
Tomato is a valuable crop around the world. Rising agricultural input costs and increased demand increases the need to investigate more efficient growing systems and improve nutrient uptake efficiency. This paper documents a project which investigated ways of improving nutrient uptake and efficiency of tomato plants in protected growing environments with the use of arbuscular mycorrhizal fungi (AMF). Micro-Tom tomato cultivar were grown in two different inorganic manufactured substrates, Rockwool and Fytocell, and an organic peat compost in a controlled environment glasshouse. Substrates were also treated with arbuscular mycorrhizal fungi (AMF). Indices of plant growth and development regarding the roots, leaves and fruits in tomato plants were measured to determine the effect of the treatments compared to the control plots. Macro- and micro-nutrient levels in the leaves and fruit were analysed post-harvest. Substrate type had a significant impact on the nutrient uptake in both fruit and leaves. Tomato grown in Fytocell produced fruit that assimilated the most nutrients. Application of AMF also had a significant impact on the nutrient uptake by fruit and leaves. Rockwool treated with AMF had a significantly higher biomass, Na and Mo levels. Further pressures on global food security are the rising world population and loss of traditional agricultural land. Therefore, it is vital to ensure that crops such as tomatoes are grown optimally. Applying this knowledge and approach to growing tomato crops could lead to more competent applications which in turn increase nutrient use efficiency and crop production.